132k views
0 votes
Convert the function into standard form:

y = (x + 4)(x - 6)

Show your work!!!

User Yang You
by
5.7k points

2 Answers

3 votes

Hey!!

What is a standard form in a quadratic equation?

... y = ax² + bx + c

In this equation, x and y are points where as a,b and c are the constants.

We have:

... y = (x+4)(x-6)

... y = (x)(x)+(x)(-6)+(4)(x)+(4)(-6)

... y = x² - 6x + 4x - 24

Combining the like terms.

... y = x² - 2x - 24 Is the standard form.

Hope my answer helps!

User Saumya Rastogi
by
5.7k points
5 votes


y = (x + 4)(x - 6)\\\\y=x^2-6x+4x-24\\\\y=x^2-2x-24

User Claytonjwong
by
5.1k points